2017
DOI: 10.3389/feart.2017.00011
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Black Carbon in the Headwaters-to-Ocean Continuum of Paraíba Do Sul River, Brazil

Abstract: Rivers annually carry 25-28 Tg carbon in the form of pyrogenic dissolved organic matter (dissolved black carbon, DBC) into the ocean, which is equivalent to about 10% of the entire riverine land-ocean flux of dissolved organic carbon (DOC). The objective of this study was to identify the main processes behind the release and turnover of DBC on a riverine catchment scale. As a model system, we chose the headwater-to-ocean continuum of Paraíba do Sul River (Brazil), the only river system with long-term DBC flux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(67 citation statements)
references
References 34 publications
10
57
0
Order By: Relevance
“…The spatial and seasonal distributions of DBC in Halong Bay suggest that riverine runoff that occurred during the wet season was efficient in mobilizing and transporting DBC to the ocean. Previous studies have reported a similar relation between salinity and the concentration of DBC (Mitra et al, 2002;Mannino and Harvey, 2004;Marques et al, 2017), with global estimates indicating that the riverine DOC pool, of which about 10% is DBC, provides an input pathway that brings about 26 Tg DBC yr -1 to the ocean (Jaffé et al, 2013). The high contribution of DBC to the pool of T-DOC in riverine flux reported in previous studies (Jaffé et al, 2013;Stubbins et al, 2015;Wang et al, 2016) is confirmed for the river system converging in Cua Luc Bay by the observed gradient of increasing DBC fraction toward the river and the high contribution of DBC to the pool of DOC (> 6% at station A) during the wet season, and by the high concentration of DBC at salinity = 0 estimated by regression analysis (about 8 µmol C L -1 ; Figure 16).…”
Section: Seasonal Dynamics (Atmospheric Versus River Inputs)supporting
confidence: 63%
“…The spatial and seasonal distributions of DBC in Halong Bay suggest that riverine runoff that occurred during the wet season was efficient in mobilizing and transporting DBC to the ocean. Previous studies have reported a similar relation between salinity and the concentration of DBC (Mitra et al, 2002;Mannino and Harvey, 2004;Marques et al, 2017), with global estimates indicating that the riverine DOC pool, of which about 10% is DBC, provides an input pathway that brings about 26 Tg DBC yr -1 to the ocean (Jaffé et al, 2013). The high contribution of DBC to the pool of T-DOC in riverine flux reported in previous studies (Jaffé et al, 2013;Stubbins et al, 2015;Wang et al, 2016) is confirmed for the river system converging in Cua Luc Bay by the observed gradient of increasing DBC fraction toward the river and the high contribution of DBC to the pool of DOC (> 6% at station A) during the wet season, and by the high concentration of DBC at salinity = 0 estimated by regression analysis (about 8 µmol C L -1 ; Figure 16).…”
Section: Seasonal Dynamics (Atmospheric Versus River Inputs)supporting
confidence: 63%
“…This would be consistent with observations of a continuous, long-term release of DPyC resulting from the degradation of historically accumulated PyC (Dittmar et al, 2012;Marques et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that PyC is much more dynamic in soils than previously thought. For example, large fluxes of dissolved PyC (DPyC, <0.7 µm particle size) in a tropical river were reported to increase during heavy rain and derive from charcoal remaining in surface soils from historical fires rather than from recent burning (Marques et al, 2017). Thus, quantifying the relative impact of historical fires on PyC stocks and export from soils is essential to understand the impact of fires on PyC stabilization in and mobilization mechanisms from soils.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cerrado study regions featured a typical degraded Cerrado landscape; agricultural land uses are interspersed with fragmented sections of natural dry forest, shrubland, and grassland. Sampling campaigns in AF2 were completed by Marques et al (2017) during three periods with differing hydrological conditions, specifically in January 2013 (wet season), August 2013 (dry season), and February 2014 (wet season). The samples collected in AF1, AF2, and AMZ1 represented headwater channels and tributaries to major rivers, with catchment areas ranging from 10 to 1,300 km 2 .…”
Section: Sampling Campaignsmentioning
confidence: 99%